Barn 8 : a novel - Unferth, Deb Olin (Graywolf, 2020)
Two auditors for the U.S. egg industry go rogue and conceive a plot to steal a million chickens in the middle of the night -- an entire egg farm's worth of animals. Janey and Cleveland -- a spirited former runaway and the officious head of audit -- assemble a precarious, quarrelsome team and descend on the farm on a dark spring evening. A series of catastrophes ensues.